Sistem Pengelolaan Surat Perintah Perjalanan Dinas di DPRD Provinsi NTB - Emil Tazahroq; Fikri Haikal; Samsul Hadi; Ariy Dermawan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The Official Travel Order (SPPD) Management System at the Regional People's Representative Council (DPRD) of West Nusa Tenggara (NTB) Province is an important innovation in enhancing the efficiency, transparency, and accountability of official travel administration. Prior to the implementation of this system, SPPD management was carried out manually, leading to various obstacles such as slow processes, administrative errors, and lack of transparency. With the adoption of an information technology-based system, the entire process from creation, approval, to reporting of SPPD can be done electronically. The system provides features for data validation, fillable templates, and automatic notifications to expedite the approval process. Integration with the regional financial system enables more efficient and accurate budget management, while a centralized database simplifies data storage and retrieval. The implementation results show significant improvements in time efficiency, reduction of administrative errors, and enhanced transparency and accountability in the use of official travel budgets. The system also facilitates better data management and supports easier audit processes. Thus, the SPPD Management System at the DPRD of NTB Province has successfully delivered positive impacts on the performance of official travel administration, creating a more productive and responsible work environment.